Data Privacy: Foundations, New Developments and the Big Data Challenge - Torra, Vicenç (Studies in Big Data, 2017)
This text offers a broad, cohesive overview of the field of data privacy. It discusses, from a technological perspective, the problems and solutions of the three main communities working on data privacy: statistical disclosure control (those with a statistical background), privacy-preserving data mining (those working with data bases and data mining) and privacy-enhancing technologies (those involved in communications and security) communities.